The prognostic significance of JAML and its role in remodeling the immune microenvironment via the cGAS-STING pathway in endometrial cancer - Tian, Chenfan; Yao, Yuanyang; Tu, Yuan; Yu, Jiaxin; Gong, Chunxia; Shi, Xiuling; Yu, Hangkun; Jiang, Peng (Frontiers in Immunology, 2026)
BackgroundEndometrial cancer (EC) is a major gynecological malignancy with a poor prognosis in the advanced stages. Junctional adhesion molecule-like protein (JAML) is gaining attention in cancer biology; however, its role in EC remains unclear.MethodsThis study integrated multi-omics data (TCGA, pan-cancer analysis and single-cell transcriptomics), dual independent clinical cohorts (TCGA dataset and an institutional cohort), and in vitro/in vivo experimental models to systematically analyze JAML expression patterns, clinical relevance, and tumor-progression regulatory mechanisms in EC. Experimental approaches included: immunohistochemistry (IHC), qRT-PCR, and Western blotting for expression validation; shRNA knockdown, Transwell/scratch assays, CCK-8 assays, and conditioned medium co-culture models for functional analysis; bioinformatics tools (ESTIMATE, TIMER, MCP-counter) and flow cytometry for immune microenvironment evaluation; drug sensitivity analysis (Genomics of Drug Sensitivity in Cancer (GDSC)/Tumor Immune Dysfunction and Exclusion (TIDE) databases) and prognostic modeling (Cox regression/nomogram) for clinical application assessment.ResultsIn EC, JAML expression was significantly downregulated and correlated with poor prognosis. JAML knockdown promoted cancer cell proliferation, migration, invasion, and epithelial–mesenchymal transition (EMT) (all P < 0.01), accompanied by reduced stimulator of interferon genes (STING) phosphorylation (P < 0.01). Low JAML expression correlated with decreased M1 (CD86+, P < 0.01) and increased M2 (CD206+, P < 0.01) macrophage infiltration. It was also linked to reduced cisplatin/paclitaxel sensitivity (P < 0.05) and lower immunotherapy response (29.04% vs. 45.05%, P = 0.015). STING agonist cyclic GMP–AMP (cGAMP) partially restored M1 infiltration and chemosensitivity after JAML knockdown in vitro. A nomogram incorporating JAML and clinicopathological parameters showed improved predictive performance (AUC 0.885; cutoff 0.882; sensitivity 0.818, specificity 0.820), with calibration curves confirming good agreement between predicted and observed recurrence.ConclusionsThese findings suggest that JAML deficiency may suppress cyclic GMP-AMP synthase (cGAS)-STING pathway activation, potentially contributing to M1/M2 macrophage polarization imbalance and facilitating EC progression. Clinically, JAML expression shows promise as a potential biomarker for prognostic stratification and treatment response prediction (chemotherapy/immunotherapy), providing insights for developing precision immunochemotherapy strategies in EC.